Profound adrenal suppression secondary to treatment with low dose inhaled steroids and itraconazole in allergic bronchopulmonary aspergillosis in cystic fibrosis. Issue 8 (1st August 2002) - Parmar, J S; Howell, T; Kelly, J; Bilton, D
Abstract : The case history is presented of a patient with cystic fibrosis in whom the treatment of allergic bronchopulmonary aspergillosis with itraconazole produced an initial response but was complicated by profound adrenal shutdown and impairment of inhaled steroid clearance resulting in paradoxical Cushing's syndrome. The authors conclude that, while it is laudable to attempt to reduce the steroid burden in any patient, it is imperative that due vigilance is exercised when using a combination of agents which interact. If such a combination therapy is embarked upon, regular assessment of the pituitary adrenal axis is advisable.